National Prosecutors Survey, 1992 ([Verlag nicht ermittelbar], 1994)
This survey queried chief prosecuting attorneys of state prosecutorial districts (district attorneys, commonwealth attorneys, etc.) about the prosecution of felony cases within their jurisdictions during 1991 and 1992. Some items included in an earlier survey, NATIONAL PROSECUTORS SURVEY, 1990 (ICPSR 9579), were repeated, covering topics such as new methods of prosecution, new kinds of evidence, use of criminal history data, general workload statistics, funding, plea negotiations, sentencing of intermediate sanctions, relationships with victims and other persons aiding prosecution, criminal defense of indigents, and the use of lower courts and grand juries. New areas of concern in 1992 included staffing, turnover, recruitment, new kinds of felonies, problem cases, scientific evidence, computerization, staff training, drug testing, and the personal risks associated with the role of prosecutor. Demographic data include sex, race, and ethnic composition of current staff members.